Students’ Perceptions of the Flipped Classroom Method in Enhancing Public Speaking Skill - Rosyidah, Rossy Halimatun (Wistara: Jurnal Pendidikan Bahasa dan Sastra, 2022)
This study aims to explore students’ perceptions of the effectiveness of the flipped classroom method in enhancing public speaking skills among fifth-semester students in the English Literature program. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with 10-15 students enrolled in the public speaking course. The interview questions were designed to elicit students’ experiences, views, and feelings regarding the use of the flipped classroom method. Additionally, a questionnaire was distributed to gather supplementary data on students’ satisfaction and engagement in the learning process. The findings indicate that students have a positive perception of the flipped classroom method. They felt that this approach provided more opportunities for participation in practical activities, such as discussions and practicing public speaking. Many students reported increased confidence and improved speaking abilities after engaging in this classroom model. They also appreciated the flexibility of self-directed learning, which allowed them to study the material before participating in class discussions.